Reproduction of fishes of the Verde River, upper Paraná River Basin, Brazil - Neves, Josias Batista (2020)
Abstract. Introduction: Understanding the various aspects of the reproductive biology of fish is a key step towards applying effective strategies for sustainable management of fishery resources. Objective: We aimed to evaluate the sex ratio, reproductive period and lengths at first maturity for 30 fish species caught in the Verde River, upper Paraná River Basin, Brazil. Methods: Fish were sampled monthly from November 2010 to March 2011 and from October 2011 to February 2012, and sampled quarterly from May to August in 2011 and 2012; totaling 14 samples. Fish were measured and weighed in the laboratory. In addition, gender and gonadal developmental stage were identified macroscopically. Subsequently, the sex ratio was determined and significant differences were tested using the chi-square (χ²) method. The reproductive period was determined with the use of gonadal developmental stages and the gonadosomatic index. Lastly, length at first maturity was estimated only for the species that presented individuals with sufficient immature and mature gonads to adjust the model. Results: Of the captured individuals, 51.5 % were male, and 48.5 % were female. Fifteen species showed significant differences in their sex ratios. The reproductive period for most species occurred from October to February, with reproductive peaks in November, December and January. The length at first maturity was estimated for only five species, including Salminus brasiliensis, a keystone species. Conclusions: The sex ratios revealed that for many species, there is a predominance of males over females, which was not expected for this parameter. The reproductive period follows the same pattern observed in Neotropical fish. However, it is noteworthy that some species are starting their reproduction in August.